Pengembangan Sistem Informasi Geografis Tentang Sebaran Penduduk Miskin Di Kabupaten Probolinggo - Hikmah, Nuzul; Marzuki, Imam; Aristi, Cici (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The implementation of this geographic information system development aims to present the distribution area of the poor in Probolinggo Regency in three dimensions in the form of a digital map. So that the information displayed is easy to analyze and can be identified the distribution of the population in a visual form. The method of developing this application uses the Software Development Life Cycle method, which consists of Planning, Analysis, Design, and Implementation. This application was created using QuantumGIS, P-mapper, and MapServer with the PHP programming language. This Geographical Information System can display the mapping of poor areas based on four levels of poverty, namely moderate poverty, near poverty, poor, and very poor. Thus, this application is very useful for the Regional Development Planning Agency of Probolinggo Regency to understand the meaning of the data that has been displayed visually on a map by looking at areas that have been grouped with the same poverty level.